Estimation of the global burden of tungiasis in endemic countries using a disability adjusted life-years modelling approach - Alistair Antonopoulos; Lynne Elson; Jürgen Krücken; Marlene Thielecke; Francis Mutebi; Richard B. Yapi; Ulrike Fillinger; Hermann Feldmeier; Ruth Nyangacha; Nono-Raymond Swar Kuispond; Eddy Kakiese Laken; Renata Santiago Alberto Carlos; et al. (BMC Global and Public Health, 2026)
Abstract Background Tungiasis is a neglected tropical zoonotic skin disease which is endemic to Sub-Saharan Africa and Latin America, caused by sand fleas of the genus Tunga , which burrow into the skin of affected humans and animals, most commonly when the feet come in contact with infested soil. Sand flea infection leads to inflammation, severe itching, and pain, with the potential for secondary bacterial or viral infections, gangrene, and disfigurement. Tungiasis disproportionately affects poor rural communities, and individuals living in unhygienic settlements. To date, the existing burden of tungiasis has never been estimated, despite being included in the World Health Organisation Neglected Tropical Diseases roadmap since 2021. Methods We applied a prevalence-based Disability Adjusted Life Year (DALY) approach focusing on Years Lived with Disability (YLD) to model the burden of human tungiasis in endemic countries. Prevalence range estimates were derived using a Bayesian hierarchical Beta-Binomial model, with probability distributions applied to represent uncertainty in estimates based on highly heterogeneous local reports, capture local and regional variation, and reflect fluctuations in symptom severity among affected individuals. A discrete time point model was implemented over a 52-week period to estimate annual DALYs lost per country included in the analysis. Monte Carlo simulation with 1000 iterations was used to generate mean DALY estimates. Results Globally, we estimate that up to 379,645 (95% UI 361,792–398,309) DALYs are lost annually, with the bulk of the burden in Sub-Saharan Africa. When comorbidities are included, this increases to 575,298 (95% UI 548,948–602,597). When adjusted for population size, we estimate that 24.2 DALYs (36.4 with comorbidities included) are lost annually per 100,000 people. In terms of DALYs lost, the disease burden is disproportionately concentrated in Sub-Saharan Africa, and Brazil. Conclusions Our estimates suggest tungiasis exerts a substantial burden of disease in endemic countries, comparable in absolute terms to that of soil-transmitted helminths and echinococcosis, and greater than that of toxocariasis, fascioliasis. Furthermore, we observe marked regional concentration of disease burden within Sub-Saharan Africa, with the disease burden in this region driven by large at-risk rural, and urban slum-dwelling, populations living within the ecological zone of transmission.